Screening of flour mill workers for respiratory morbidities: a cross-sectional study in rural Bangalore - P., Seema; Kumar M., Shashi; R., Deepthi (International Journal Of Community Medicine And Public Health, 2020)
Background: Flour mill workers are highly exposed to organic wheat flour dust with a large diversity of antigenic/allergic component leading to respiratory morbidity and skin allergies. This work environment may affect workers health and safety if the effects are unchecked periodically. Methods: A cross-sectional study was conducted among 194 workers of 4 flour mills in Bangalore Rural district. Prior permission (factory) and informed consent *(workers) were obtained. Pre-structured interview-schedule was administered. Peak expiratory flow rate (PEFR) readings were measured by using wrights flow meter and best of 3 readings recorded. Respiratory morbidity was assessed on PEFR classification - based on American lung association (ALA) colour coding - red, yellow and green zones. Respiratory morbidity was compared with years of experience, type of work, smoking habits and usage of appropriate PPEs. Data was analyzed using Epi-info 08. Results: Among 194 workers studied, 188 were males, 6 were females. They were in the age group of 15-50 years. 143 (73.7%) were engaged in work with direct dust exposure. 84 (43%) were working for more than 3 years, 50 (25%) between 1-3 years and 60 (30%) for less than a year. 7.2% regularly smoked. According to ALA classification, PEFRs of 71 (36%) of the workers were classified into RED, 91 (46%) to yellow and 32 (16%) to green zones respectively. Usage of PPEs was only among 126 (64%). Conclusions: Respiratory morbidity among flour mill workers was high. Adequate use of PPEs was low. Half of the workers fell into yellow zone that had a potential to fall into red zone if external factors were not considered.